2006
DOI: 10.1007/s00221-006-0750-x
|View full text |Cite
|
Sign up to set email alerts
|

The “ways” we look at dreams: evidence from unilateral spatial neglect (with an evolutionary account of dream bizarreness)

Abstract: Despite decades of research, the question of whether the rapid eye movements (REMs) of paradoxical sleep (PS) are equivalent to waking saccades and whether their direction is congruent with visual spatial events in the dream scene is still very controversial. We gained an insight into these questions through the study of a right brain damaged patient suffering attentional neglect for the left side of space and drop of the optokinetic nystagmus (OKN) with alternating rightward slow/leftward fast phases evoked b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Therefore, we cannot directly aYrm the relationship between the direction of REMs and the gaze of the dreamer at the dream scene, as proposed in the "scanning hypothesis" (Dement and Kleitman 1957). In relation to the scanning hypothesis, however, Doricchi et al (2007) recently reported that a left unilateral neglect patient showed the selective disappearance of the optokinetic nystagmus (OKN) and Nystagmoid-REMs in one horizontal direction, suggesting that morphologically diVerent types of REMs exist in humans: Nystagmoid-REMs, which share phylogenetically ancient oculomotor mechanisms with OKN, and otherwise. V1 showed distinct activation in both the event-related analysis and the time-course analysis.…”
Section: Activation Preceding Remmentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, we cannot directly aYrm the relationship between the direction of REMs and the gaze of the dreamer at the dream scene, as proposed in the "scanning hypothesis" (Dement and Kleitman 1957). In relation to the scanning hypothesis, however, Doricchi et al (2007) recently reported that a left unilateral neglect patient showed the selective disappearance of the optokinetic nystagmus (OKN) and Nystagmoid-REMs in one horizontal direction, suggesting that morphologically diVerent types of REMs exist in humans: Nystagmoid-REMs, which share phylogenetically ancient oculomotor mechanisms with OKN, and otherwise. V1 showed distinct activation in both the event-related analysis and the time-course analysis.…”
Section: Activation Preceding Remmentioning
confidence: 97%
“…On the basis of their Wndings, they showed that morphologically diVerent types of REMs exist in human REM sleep. Although their results and "evolutionary hypothesis" (Doricchi et al 2007) are intriguing, they…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these experiments were based on small sample sizes and the results have not been replicated in subsequent experiments. Doricchi et al (2006) claim that “despite decades of research, the question of whether the REMs of paradoxical sleep (PS) are equivalent to waking saccades and whether their direction is congruent with visual spatial events in the dream scene is still very controversial”. According to Hobson et al (2000), “further evidence would be required to confirm [the scanning] hypothesis”.…”
Section: Room For Skepticism: What the Received View Does Not Explainmentioning
confidence: 99%